Masuda's sandstone core hydrate dissociation experiment revisited. (16th January 2018) - Hardwick, Jack S.; Mathias, Simon A.
Highlights: A fully coupled numerical model for transport and hydrate dissociation is presented. The model is able to reconcile fluid production, pressure and temperature data. Permeability is found to be significantly reduced by very low hydrate saturations. Abstract: Numerical simulation of hydrate dissociation in porous media is important to investigate future hydrate fuel extraction strategies and/or the impacts of climate change on the long-term stability of vulnerable near-surface hydrate deposits. The core-scale hydrate dissociation experiment of Masuda et al. (1999) represents an important experimental data set that can be used for benchmarking numerical simulators for this purpose. Data collected includes gas production, water production, boundary pressure and temperature from three internal observation points. At least six modeling studies exist within the literature seeking to simulate the gas production data and the temperature data. However, the pressure data and water production data are generally overlooked. In this article we present a set of numerical simulations capable of reconciling the Masuda et al. (1999) data set in its entirety. Improvements on existing modeling studies are achieved by: (1) using improved estimates of the initial hydrate saturation; (2) obtaining relative permeability parameters, a hydrate stability depression temperature and a convective heat transfer coefficient by calibration with the observed data; and (3) applying a new critical threshold permeability model, specifically to reconcile a relatively fast gas production with a relatively slow far-field boundary pressure response. A subsidiary finding is that permeability is significantly reduced in the presence of very low hydrate saturations. But more importantly, the multi-faceted effectiveness of the data set from Masuda's experiment is clearly demonstrated for numerical simulation benchmarking in the future.